Investigations on degradation of the long-term proton exchange membrane water electrolysis stack - Sun, S.; Shao, Zongping; Yu, H.; Li, G.; Yi, B. (Elsevier SA, 2014)
A 9-cell proton exchange membrane (PEM) water electrolysis stack is developed and tested for 7800 h. The average degradation rate of 35.5 μV h−1 per cell is measured. The 4th MEA of the stack is offline investigated and characterized. The electrochemical impedance spectroscopy (EIS) shows that the charge transfer resistance and ionic resistance of the cell both increase. The linear sweep scan (LSV) shows the hydrogen crossover rate of the membrane has slight increase. The electron probe X-ray microanalyze (EPMA) illustrates further that Ca, Cu and Fe elements distribute in the membrane and catalyst layers of the catalyst-coated membranes (CCMs). The cations occupy the ion exchange sites of the Nafion polymer electrolyte in the catalyst layers and membrane, which results in the increase in the anode and the cathode overpotentials. The metallic impurities originate mainly from the feed water and the components of the electrolysis unit. Fortunately, the degradation was reversible and can be almost recovered to the initial performance by using 0.5 M H2SO4. This indicates the performance degradation of the stack running 7800 h is mainly caused by a recoverable contamination.